The therapeutic effects of microRNAs in preclinical studies of acute kidney injury: a systematic review protocol - Zankar, Sarah (Syst Rev, 2019)
BACKGROUND: Acute kidney injury (AKI) causes significant morbidity and mortality in humans, and there are currently no effective treatments to enhance renal recovery. MicroRNAs (miRNAs) are short chain nucleotides that regulate protein expression and have been implicated in the pathogenesis of AKI. Recently, preclinical studies in vivo have uncovered a therapeutic role for administration of specific miRNAs in AKI. However, the overall benefits of this strategy in preclinical studies have not been systematically reviewed, and the potential for translation to human studies is unclear. AIM: The primary aim is to conduct a systematic review of the therapeutic properties of miRNAs in preclinical studies of AKI. The secondary aim is to determine potential adverse effects of miRNA administration in these studies. METHODS: A comprehensive search strategy will identify relevant studies in AKI in vivo models, using the MEDLINE, EMBASE, OVID, PUBMED, and Web of Science databases. The search strategy will include terms for mammalian (non-human) AKI models, including injury related to ischemia/reperfusion, nephrotoxicity, sepsis, contrast agents, cardio-pulmonary bypass, and hemorrhagic shock. Interventions will be defined as direct administration of exogenous miRNAs or antagonists of miRNAs, as well as maneuvers that alter expression of miRNAs that are mechanistically linked to AKI outcomes. The primary outcomes will be indices of kidney function and structure, and there will be no restriction on comparator interventions. Two independent investigators will initially screen abstracts, and selected articles that meet eligibility criteria will be reviewed for data abstraction and analysis. The SYRCLE RoB tool for animal studies will determine risk of bias, and meta-analysis will be performed as appropriate. The GRADE methodology will assess the quality of evidence. DISCUSSION: The administration of selective miRNA mimics or antagonists exerts beneficial effects in mammalian models of AKI, although multiple obstacles must be addressed prior to translation to human clinical trials. The proposed systematic review will document key miRNA candidates, and determine effect size estimates and sources of outcome bias. The review will also identify gaps in knowledge and guide future directions in AKI research. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42019128854